Selective hydrosiloxane synthesis via dehydrogenative coupling of silanols with hydrosilanes catalysed by Fe complexes bearing a tetradentate PNNP ligand. Issue 47 (21st November 2018) - Takeshita, Tomohiro; Sato, Kazuhiko; Nakajima, Yumiko
Abstract : Iron complexes bearing PNNP efficiently catalyse dehydrogenative coupling of silanols with silanes to selectively form various hydrosiloxanes. Abstract : A well-defined iron complex system was established using PNNP-R (R = Ph and Cy) as a strong σ-donating ligand with a rigid meridional tetradentate structure. Reactive Fe(0) complexes [Fe(PNNP-R)2 (μ-N2 )] were synthesized by a reaction of the corresponding iron dihalide with NaBEt3 H and structurally characterized. The reaction proceeded via the iron dihydride intermediate [Fe(H)2 (PNNP-R)], which underwent H2 reductive elimination, supporting the hemilabile behavior of PNNP-R. [Fe(PNNP-R)2 (μ-N2 )] catalyzed the dehydrogenative coupling of silanols with silanes to selectively form various hydrosiloxanes, which are important building blocks for the synthesis of a range of siloxane compounds. This system exhibited higher catalytic efficiency than the previously reported precious-metal-catalyzed systems.